Desain Prototipe Pemberi Pakan Otomatis Untuk Kucing Peliharaan Berbasis Internet of Things (IOT) dengan Fitur Monitoring Real Time - Hani Rifdah Azizah; Joni Maulindar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The need for regular feeding of pets, especially cats, presents a challenge for owners with busy schedules. Irregular feeding can negatively impact the animal's health. This research aims to design a prototype of an automatic pet feeder based on the Internet of Things (IoT) with real time monitoring and control features. The system is developed using an ESP32 microcontroller, HX711 load cell sensor, servo motor, RTC DS3231 real time clock module, vibration sensor, and the Blynk application as a remote interface. The method used is the Prototype model. The system operates in two modes: automatic mode using the schedule from the Blynk app and offline automatic mode using a default schedule from the RTC when not connected to the internet. Additionally, a manual mode is available via a physical button. The system is tested for both hardware and software functionality, as well as automation performance. Results show the system can dispense food on schedule with good accuracy and display real time status via an OLED screen and the Blynk app. This system is expected to be an efficient and flexible solution for pet owners in managing automated feeding..